Peningkatan Status Gizi Balita Gizi Kurang Melalui Pendampingan dan Pemberian Makanan Tambahan (PMT) - Tutut Pujianto; Cucuk Suprihartini (STIKES dan AKZI Karya Husada Kediri, 2022)
Supplementary Feeding (PMT) is one way to prevent malnutrition. PMT can take advantage of local food around the house. PMT must be designed according to its needs and designations. Community service activities carried out by lecturers and students aim to help deal with malnourished toddlers through mentoring and providing PMT. Community service activities were carried out in Turus Village, Gurah District, Kediri Regency, by providing assistance and PMT for 14 consecutive days, starting from February 17 to March 16, 2022. The PMT given to malnourished toddlers is an innovation of students and lecturers of the Academy of Nutrition Karya Husada Kediri. The creation of the PMT menu is based on the results of the recall of the nutritional status of the toddler as well as the needs for energy, protein, fat, and carbohydrates that should be needed by toddlers. During the 14 days of PMT menu provision, the team assisted while toddlers consumed PMT, as well as provided education to toddler mothers about the benefits of PMT and how to make PMT. Evaluation of PMT results is carried out by comparing the weight of the toddler before and after PMT. The results of the evaluation of changes in the body weight of toddlers after 14 days of mentoring experienced an average increase of 0.48 kg. PMT to toddlers who are always different can overcome boredom, so the leftovers produced are only around 10%-15%. The effectiveness of large enough community service activities needs to be continued in other areas that have the same problem.